Penggunaan Media Android dalam Pembelajaran Sistem Sirkulasi Kelas XI SMA - Nur, Miftah Saddatin; Langi, Indriani Limbong; Hardianto, Hardianto (Biology Teaching and Learning, 2019)
Abstract. The use of learning media is something that cannot be separated and is already an integration of the learning methods used, learning media can explain what the teacher is not able to say through words, so abstractness is in accordance with the existing concepts. This study aims to study how the influence of the use of android-based learning media on learning biology circulating class XI SMA. By using android students can better understand the concepts in learning, can repeat lessons that do not need to consider from face to face time in class, and can also make students to learn independently because of the availability of subject matter that can be accessed using Android. The results of this study prove that the incorporation of android in learning can attract students' interest and motivation in learning and also help students understand the concepts in the circulation system and can make students learn independently. Keywords: android, biology learning, circulation system.